Nonlocal Third Order Boundary Value Problems with Solutions that Change Sign - Sergey Smirnov (Mathematical Modelling and Analysis, 2014)
We investigate the existence and the number of solutions for a third order boundary value problem with nonlocal boundary conditions in connection with the oscillatory behavior of solutions. The combination of the shooting method and scaling method is used in the proofs of our main results. Examples are included to illustrate the results.